Short-term treatment of osteoarthritis-induced sheep with human umbilical cord–derived mesenchymal stem cells: A morphological and proteomic analysis - Kusdiantoro Mohamad; Adrian Situmeang; Handina Rakhmawati; I Ketut Mudite Adnyane; Mokhamad Fahrudin; Nurhidayat Nurhidayat; Harry Murti; Andri Maruli Tua Lubis; Arief Boediono (Jurnal Medik Veteriner, 2026)
Knee joints are the primary sites affected by osteoarthritis (OA) in humans and animals. Although intra-articular human umbilical cord–derived mesenchymal stem cells (hUC-MSCs) show therapeutic promise, their combined use with hyaluronic acid (HA) remains underexplored in large animals. This study evaluated morphological and proteomic changes in a sheep osteoarthritis model treated with both agents. A total of twelve sheep were divided into four groups (n = 3 per group): control (normal and OA) and three treatment groups receiving hUC-MSCs, HA, or a combination of HA and hUC-MSCs (HA + hUC-MSCs). OA was induced by meniscectomy, and intra-articular injections were administered four weeks post-surgery. Macroscopic scoring was conducted according to the Osteoarthritis Research Society International system, while histological evaluation was performed using hematoxylin–eosin, Safranin O, and Masson’s trichrome staining. Proteomic analysis of synovial fluid was carried out using liquid chromatography–tandem mass spectrometry. The macroscopic OA score in the HA + hUC-MSC group was lower than in the other treatment groups and was not significantly different from the normal group (p > 0.05). Microscopic observations indicated that hUC-MSCs supported joint cartilage regeneration by preserving proteoglycan and collagen content. Proteomic profiling revealed that treatment with HA + hUC-MSCs modulated proteins associated with complement activation and coagulation pathways. The combination of HA and hUC-MSCs provided synergistic benefits for cartilage regeneration in a sheep OA model during a short treatment period. These findings suggest that this approach represents a promising regenerative therapy for OA in large animals within veterinary medicine and has translational relevance for human regenerative medicine.